LVTree Viewer: An Interactive Display for the All-Species Living Tree Incorporating Automatic Comparison with Prokaryotic Systematics - Guanghong Zuo; Xiaoyang Zhi; Zhao Xu; Bailin Hao (Genomics, Proteomics & Bioinformatics, 2016)
We describe an interactive viewer for the All-Species Living Tree (LVTree). The viewer incorporates treeing and lineage information from the ARB-SILVA website. It allows collapsing the tree branches at different taxonomic ranks and expanding the collapsed branches as well, keeping the overall topology of the tree unchanged. It also enables the user to observe the consequence of trial lineage modifications by re-collapsing the tree. The system reports taxon statistics at all ranks automatically after each collapsing and re-collapsing. These features greatly facilitate the comparison of the 16S rRNA sequence phylogeny with prokaryotic taxonomy in a taxon by taxon manner. In view of the fact that the present prokaryotic systematics is largely based on 16S rRNA sequence analysis, the current viewer may help reveal discrepancies between phylogeny and taxonomy. As an application, we show that in the latest release of LVTree, based on 11,939 rRNA sequences, as few as 24 lineage modifications are enough to bring all but two phyla (Proteobacteria and Firmicutes) to monophyletic clusters.